In vitro antimicrobial activity of ceftolozane/tazobactam against Pseudomonas aeruginosa and other non-fermenting Gram-negative bacteria in adults with cystic fibrosis. (September 2018) - Gramegna, A.; Millar, B.C.; Blasi, F.; Elborn, J.S.; Downey, D.G.; Moore, J.E.
Highlights: Ceftolozane/tazobactam (C/T) is a new cephalosporin/β-lactamase inhibitor antimicrobial combination. C/T has activity towards non-fermenting Gram-negative bacteria. C/T has good in vitro activity against cystic fibrosis clinical Pseudomonas aeruginosa compared with other antimicrobials. C/T has no activity against Burkholderia cenocepacia or Achromobacter xylosoxidans . Abstract: Objectives: Pulmonary exacerbations in patients with cystic fibrosis (CF) caused by chronic Gram-negative bacterial infections are associated with reduced survival. These pathogens are usually treated with repeated courses of systemic antimicrobial agents. However, there is associated emergence of multidrug-resistant (MDR) pathogens. Ceftolozane/tazobactam (C/T) is a novel cephalosporin/β-lactamase inhibitor combination that has been demonstrated to have good activity against MDR Pseudomonas aeruginosa . Methods: In this study, C/T was compared with other commonly used intravenous antimicrobial agents against 193 non-fermenting Gram-negative bacteria isolated from CF sputum specimens, including P. aeruginosa, Achromobacter xylosoxidans, Stenotrophomonas maltophilia and Burkholderia cenocepacia . Minimum inhibitory concentrations (MICs) to C/T were determined by standard Etest assay and were interpreted according to current European Committee on Antimicrobial Susceptibility Testing (EUCAST) guidelines. Results: C/T had good in vitro antimicrobial activity against CF clinical isolates of P. aeruginosa in comparison with other antimicrobial agents, with the exception of colistin. C/T also had activity against S. maltophilia but was not active against B. cenocepacia or A. xylosoxidans . Conclusion: C/T showed excellent in vitro activity against P. aeruginosa CF clinical isolates. This antimicrobial agent is a potential therapeutic option when presented with challenging MDR P. aeruginosa and S. maltophilia exacerbations. Further clinical experience and trials in CF are required to determine the place of C/T in clinical practice.